Exploring Work Satisfaction and Characteristics of Iraqi Pharmacist Workforce - Ali Azeez Al-Jumaili; Zayneb Ahmed Mohammed; Mohammed Jamal Yawuz; Kawther Khalid Ahmed (Brazilian Journal of Pharmaceutical Sciences, 2022)
Abstract The objectives of this study were to describe work characteristics of Iraqi pharmacists, to compare pharmacist job satisfaction between private and public sectors and to assess factors influencing job satisfaction level. This cross-sectional study of pharmacists, their work sites and work satisfactions used an electronic questionnaire that was posted on Facebook pharmacy professional group from June to September 2018. The participants included pharmacists from all 18 Iraqi provinces. We used multiple linear regression to identify predictors of general job satisfaction among 13 pharmacist characteristics. We received 658 usable surveys. Approximately half (47.24%) of respondents indicated dissatisfaction with their primary workplace. Job performance, patient contact, satisfaction with manager, income and expectation satisfactions were significantly related with work satisfaction. Pharmacists working in the private sector had significantly more control over their workplace and higher satisfaction with manager, income and general satisfactions compared to those working in public sector. Pharmacists work in diverse settings across the public healthcare system, community pharmacies, private drug bureaus and academia. About half of them are dissatisfied with their primary workplace. The private sector has more satisfaction rate compared to the public sector. Thus, officials need to improve job environments in the public sector.